Trash Becomes Valuable Goods: Training in Making Unique Home Decorations from Household Waste - Ria Novianti; Roza Linda; Nana Rahayu; Ni Putu Wijayanti; Ainama Nafisa Putri; Farah Nurhaliza (Asosiasi Profesi Multimedia Indonesia, 2025)
Background: The problem of the lack of productive skills among housewives is a challenge in efforts to improve family welfare and empower the community's potential. To overcome this, training was conducted on how to make home decoration crafts from household waste.Aims: The purpose of this activity aims to improve the skills of housewives in processing waste into valuable and aesthetic products, as well as to open up creative business opportunities.Methods: The training method is participatory and gradual, starting with introducing waste types, processing techniques, and direct practice in making decorative crafts.Result: The evaluation results through pretest and posttests showed a significant increase by 95.62% in the ability of participants to make home decoration crafts. This increase reflects the effectiveness of the applied training method.Conclusion: With these results, it can be concluded that this training has succeeded in achieving its objectives, and the skills obtained are expected to encourage participants' economic independence through recycled craft-based entrepreneurship.